Tutoring in higher education. A historical approach - Navarrete-Cazales, Zaira; Tomé López, Jade (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: to identify the historical, social and political events that gave rise to the conformation of tutoring at the higher education level, specifically in Mexico. Originality/contribution: The originality of this work lies in the historical tracing carried out to find the emergence and origin of tutoring in higher education, using the Foucauldian genealogy as a method. Method:The collection of information was carried out through a review of the documentary bibliography based on a socio-historical analysis of tutoring in higher education. Strategies/information collection:  Documentary collection and analysis. Conclusions: Some of the conclusions are: 1) Mentoring linked to education has been present since ancient times. 2) The current conceptualization of tutoring is linked to terms such as: guide, ayo, counselor, instructor, governess, preceptor, teacher, priest, parent. 3) Tutoring has gone through different periods until reaching modern times, as a support or guide, mostly for teachers -although also for students- that has served to complement the academic performance of the tutored. 4) In Mexico, tutoring has its origins in the 19th century, in the Lancasterian schools. 5) Although tutoring was formerly considered as a moral guide, it has changed to be considered nowadays as an integral support that, by solving academic, personal or family issues, and even, sometimes, economic, contributes to improve the student's academic performance. This is how tutoring has been consolidated in the educational field.